Rodna perspektiva u istraživanjima manjinskih vjerskih zajednica: Derviška zajednica u Rijeci - Rubić, Tihana (2008)
The author sets focus on ethnic and religious identity of Muslim minority and the group of dervishes in Croatia, particularly on women's role in a ritual. She is interested in how women's spirituality and religiosity is constructed and obtained, and what part is eventually determined by silence or oppression.